2019
DOI: 10.2340/00015555-3307
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Efficacy Increases with the Repetition of Botulinum Toxin A Injections in Primary Axillary Hyperhidrosis: A 15-year Study in 117 Patients

Abstract: Future studies could focus on patients with a decrease in DE, in order to identify the risk factors for the type of this evolution or the differences between responder and non-responder patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…They speculated that the increase in duration and efficacy of injection repetitions were related to the gradual regeneration of the axon terminal of the motor neuron. Berthin and Maillard recently confirmed these findings with a retrospective 15-years study on 117 patients [29].…”
Section: Resultssupporting
confidence: 53%
“…They speculated that the increase in duration and efficacy of injection repetitions were related to the gradual regeneration of the axon terminal of the motor neuron. Berthin and Maillard recently confirmed these findings with a retrospective 15-years study on 117 patients [29].…”
Section: Resultssupporting
confidence: 53%
“…Interestingly, two previous studies have shown that the duration of efficacy of BoNT-A treatment for axillary hyperhidrosis increases with treatment repetition. 16,17 In conclusion, abobotulinum toxin-A is more frequently used in daily practice because it is more cost-effective. Facial wrinkles, platysmal bands, and masseter hypertrophy are the most commonly desired-to-be-treated areas.…”
Section: Discussionmentioning
confidence: 99%
“…These data are similar to those reported for BoNT injections for the treatment of hyperhidrosis. During long-term follow-up, it was found that repeated injections increased the duration of efficacy by more than 50% [26]. Further longterm studies are required to identify the duration of response in subjects with sialorrhea.…”
Section: Discussionmentioning
confidence: 99%